1 X 1000 kVA Transformer Measurement Analysis using Dyn-11 Vector Group and Off Load Tap Changer - Setiyo Budiyanto; Lukman Medriavin Silalahi; Freddy Artadima Silaban; Adi Kurnia; Agus Dendi Rochendi; Muhammad Budi Haryono; Mochamad Furqon Ismail (Journal of Integrated and Advanced Engineering (JIAE), 2021)
The transmission line of electrical energy generated by the power plant is usually located far from the load center to be distributed to the community. The substation is part of a distribution transmission line that acts as a control center and consists of a collection of extra high voltage equipment. Routine maintenance of the power transformer as the main equipment of the substation must be scheduled so that its performance remains reliable. The proposed method of this research is to analyze the condition of the transformer through testing when it is off, to the calculation of the transformer ratio to determine the condition of the transformer windings using the calculation of the formula and measurement of the Raytech Transformer Turn Ration measuring instrument. In this research, the Raytech Transformer Turn Ratio measurement tool is used to determine the ratio of the winding input voltage of 20,000 volts and the output voltage of 400 volts on the power transformer. At a voltage of 40VAC, from the results of the comparisons that have been made, it can be seen that the test results of the Raytech Transformer Turn Ratio measuring instrument, if it crosses the 0.5% tolerance limit, the measurement results on one of the coils change the ratio. If the transformer is not regularly checked, the impact will result in unbalance of voltage on one of the coils. And one of the coils in phase will expand and cause a loss of voltage.